Improving Adolescent Health Through the Implementation of Date Milk Consumption to Increase Hemoglobin Levels - Mahmudah, Siti; Trisnaningsih, Rahma (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Anemia is a health problem that is often found in teenagers with a prevalence of 32%. Anemia in adolescents has a negative impact on growth, development, cognitive abilities and learning concentration, as well as increasing susceptibility to infectious diseases. The causes of anemia in teenagers include lack of intake of nutrients needed for the formation of hemoglobin, namely energy, protein, iron (Fe), and vitamin C. Dates are rich in calcium and iron. Consuming date milk regularly can help the body have enough iron, thereby reducing the risk of anemia. Objective to determine HB levels before and after giving date milk and to find out the difference in average HB levels in teenagers before and after giving date milk. This type of research uses a quasi experiment with a two group pre and post test with control design. The research subjects were 32 teenagers consisting of treatment and control groups. The treatment group was given date milk at a dose of 300 ml/day for 7 days, while the control group was not given it. Data analysis used the independent t-test. The average hemoglobin level in the treatment group increased by 0.72 g/dL, while in the control group there was a decrease in hemoglobin level by 2.78 g/dL with a ρ value of 0.000 < alpha 0.05 so there was a significant difference between the average hemoglobin level before and after giving date milk. Consuming 300 ml of date milk/day for 7 days can increase hemoglobin levels in adolescents.